Diseminasi Alat Pengering Tepung Labu Ekonomis berbasis Internet of Things (IoT) pada Kelompok Wanita Tani Kreasi Karya Mandiri Jekulo Kudus - Mohammad Riza Radyanto; Endang Tjahjaniningsih; Dewi Handayani (Universitas Maritim AMNI Semarang, 2023)
The Kreasi Karya Mandiri Women's Farmers Group (KWT) is a pumpkin cultivator in Bulung Cangkring Village, Jekulo District, Kudus Regency, with 12 members. They supply fresh pumpkin flour to Micro, Small, and Medium Enterprises (MSMEs) that produce Pumpkin Flour. The problem is that when drying pumpkin flour ingredients it still depends on sunlight, where during the dry season the drying can be optimal, but on the other hand, during the rainy season the sunlight is uncertain. Apart from that, drying in the sun is very unhygienic because the air is in the open and from a safety perspective food is very unsupportive. This service aims to 1. Assist in the application of appropriate technology in the form of a dryer equipped with an automatic controller. 2. Provide knowledge to members about the importance of increasing business productivity and product hygiene. Methods used: face-to-face training and socialization about The role of artificial intelligence in the agricultural sector. It is hoped that the results of this activity will allow KWT members to understand and understand the importance of implementing the Internet of Things (IoT).